Armee abschaffe! - [Matterhorn mit Sonne dahinter]
politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Friedensbewegung politischer Rahmen;politisches Leben (allgemein);politische Ideologie;Pazifismus Sicherheitspolitik;Verteidigung;Armee;Armeeabschaffung;GSoA